Novel properties of Hippophae rhamnoides L. twig and leaf extracts - anti-virulence action and synergy with antifungals studied in vitro on Candida spp. model. (June 2017) - Sadowska, Beata; Budzyńska, Aleksandra; Stochmal, Anna; Żuchowski, Jerzy; Różalska, Barbara
Abstract: Original, chemically characterized Sea buckthorn (SBT) twig and leaf extracts were in vitro studied in terms of anti- Candida activity. Minimum inhibitory concentrations (MICs) of the extracts against C. albicans ATCC 10231 ranged: 250 μg/ml (twig), 31.5 μg/ml (leaf), and against C. glabrata G1 (clinical isolate) - 15.6 μg/ml (twig), 3.9 μg/ml (leaf). Next the extracts have been used at their subMIC. Both extracts significantly enhanced activity of fluconazole (FLC) and caspofungin (CAS) against C. albicans and increased their efficacy against C. glabrata, measured by an agar dilution assay combined with the E-test. The extracts inhibited C. albicans morphogenesis such as germ tube and hyphae formation as well as invasion to the " Spider " Agar. Antiadhesive and anti-biofilm activities of the extracts were evaluated by Alamar Blue reduction assay. It showed not significant reduction in the degree of cell adhesion (by 10–15%) but noticeable decrease of biofilm formation (by 80% in the case of SBT-twig extract). In conclusion, this study provided the evidence that SBT extracts, used at non-cytotoxic concentrations for the fibroblasts (IC50 from 664.8 μg/ml to 1060.4 μg/ml), targeted some of Candida spp. virulence factors essential for the establishment of the infection. SBT twigs, previously regarded as waste material, were shown to be also a valuable source of the substances with promising antimicrobial activity. Graphical abstract: Highlights: Novel biological properties of sea buckthorn (SBT) twig and leaf extracts were described. SBT extracts demonstrated synergy with antifungals against Candida spp. SBT extracts exhibited an effect on yeast morphogenesis and biofilm formation. SBT extracts may be considered as plant products with virulence-modifying activity. Proanthocyanidins-rich twig extract is a valuable source of antifungal substances.